From Social Media to Experience: A Digital Marketing Model for Tourism Destination in Bandung Regency - Fadhlurrahmah, Sitti Nur Azmi; Suhartanto, Dwi; Azzahra, Sopia Gina (Journal of Tourism Sustainability, 2025)
This study develops and tests a social-media–driven model explaining how destination social-media promotion shapes destination image and attractiveness, enriches tourist experience quality, and drives in revisit intention to tourism destination in Bandung Regency. A quantitative, cross-sectional survey of recent visitors was analyzed using PLS-SEM to estimate the measurement and structural relations. Results show that social-media promotion significantly improves destination image and attractiveness; both subsequently strengthen experience quality, which emerges as the strongest predictor of revisit intention. Reliability and validity diagnostics meet recommended thresholds, and the model explains a substantial share of variance in revisit intention. As a managerial output, the paper proposes a digital tourism marketing model that operationalizes the verified pathway by integrating S-O-R with the AIDA journey—translating attention and interest captured online into desire and action, then aligning on-site delivery with expectations formed on social media to convert engagement into repeat visitation.